Perspectives of Contributing Factors and Prevention Measures of Struck-by Accidents in from Experienced Safety Personnel - Mohd Shahar , Nurshamimi; Abas, Nor Haslinda; Basirun, Nurul Fasihah; Memon, Mujtaba Hassan (International Journal of Sustainable Construction Engineering and Technology, 2023)
Malaysia’s construction industry has been long characterized as risky, as evidenced by its poor health and safety performance. The statistics on fatal accidents recorded by the Department of Safety and Health Malaysia (DOSH) present that struck by accident in the Malaysian construction industry have the highest number of deaths and were one of the critical contributor. Therefore, this study was done to find the main contributing factor to the struck by accidents and its preventive measures. The questionnaire was distributed to the respondents, who were experienced safety personnel in construction industry with at least 10 years’ experience in handling safety and health at the workplace. From the questionnaire survey, the most significant contributing factor to struck-by accidents is careless behaviour, and the main perceived prevention measure for struck-by accident is job hazard analysis or job safety analysis briefing to workers before starting job. The outcome of the study could provide awareness on struck-by accidents and reduce the risk of struck-by accident by objects in the construction industry in Malaysia.